2022
DOI: 10.1111/dth.15353
|View full text |Cite
|
Sign up to set email alerts
|

Progressive digital necrosis during gemcitabine/nab‐paclitaxel chemotherapy in a patient with pancreatic cancer

Abstract: Progressive digital necrosis during gemcitabine/nab-paclitaxel chemotherapy in a patient with pancreatic cancer Dear Editor, Chemotherapy rarely induces digital necrosis in a patient with malignant neoplasms. 1 We report the second case of digital necrosis, which occurred during gemcitabine/nab-paclitaxel combination therapy and progressed after withdrawing chemotherapy. F I G U R E 1 (A) At the initial visit, her left 4th finger had cyanosis. Two weeks later, the tip of the left 4th finger became necrotic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In this case, fluorometholone eye drops and the patient’s supine posture might contribute to skin necrosis. Another study reported progressive digital necrosis during gemcitabine/nab-paclitaxel chemotherapy in a patient with pancreatic cancer [4].…”
Section: Introductionmentioning
confidence: 99%
“…In this case, fluorometholone eye drops and the patient’s supine posture might contribute to skin necrosis. Another study reported progressive digital necrosis during gemcitabine/nab-paclitaxel chemotherapy in a patient with pancreatic cancer [4].…”
Section: Introductionmentioning
confidence: 99%